DEVELOPMENT OF IPAS PROJECT E-MODULES THROUGH A PROJECT-BASED LEARNING (PJBL) APPROACH TO IMPROVE SCIENTIFIC LITERACY, ON SUBSTANCE MATERIALS AND THEIR CHANGES - Hutahaean, Rita Donna; Siregar, Tiurlina; Siallagan, Johnson; Ortis Fredy Waromi (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2026)
Development of the IPAS Project e-module through the Project Based Learning (PjBL) approach to improve scientific literacy in substance materials and their changes. The objectives of the research are (1) designing e-modules through the PjBL approach, (2) Feasibility analysis of e-modules, (3) Evaluation of improving scientific literacy. The research method used is Research and Development (R&D) with a 4D (Define, Design, Develop, Disseminate) development model. The research was conducted at the Papua Special Tourism State School with a total of 30 students. The results of the study show that: (1) E-modules through the PjBL approach are made through the first stage is definition, the second is data collection, the third is making a module design, the fourth is validating the model design, the fifth is revising the module design, the sixth is a small-scale trial, then a large-scale trial to obtain scientific literacy data in learning, as well as the response of IPAS Project teachers to the module. (2) The feasibility analysis of the e-module was obtained through validation of validators (92.36% of the category strongly agreed), peer feasibility test (94.65% of the category strongly agreed) so that it was declared very feasible to use (3) The evaluation of scientific literacy improvement was obtained that the increase in scientific literacy increased in RPP 1 by 15.53%, in RPP 2 by 45.13%, in RPP 3 by 52.24% with an average value increase in the three meetings of 35.86% after using the module The IPAS project in learning so that significantly the application of e-modules through PjBL is effectively used as a contextual learning medium at the vocational school level.